2016
DOI: 10.7717/peerj.2633
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and risk of fatty liver disease: a meta-analysis

Abstract: BackgroundObservational studies have shown inconsistent results regarding alcohol consumption and risk of fatty liver. We performed a meta-analysis of published literature to investigate the association between alcohol consumption and fatty liver disease (FLD).MethodsWe searched Medline, Embase, Web of Science, and several Chinese databases, identifying studies that reported an association between alcohol consumption and the risk of FLD.ResultsA total of 16 studies with 76,608 participants including 13 cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
26
0
2
Order By: Relevance
“…(32) In a 2016 meta-analysis of mostly cross-sectional studies with a total of 76,608 participants, drinking alcohol up to 40 g per day was associated with a 23% reduction in prevalence of fatty liver disease. (33) In a recent prospective study of a healthy Japanese population without liver disease at baseline who were followed for up to 3 years, drinking alcohol (up to more than 40 g per day for men and 20 g per day for women) was associated with decreased incidence of fatty liver diagnosed by ultrasound imaging. (21) In a cross-sectional study of baseline data for adult patients in the Nonalcoholic Steatohepatitis Clinical Research Network with biopsy-proven NAFLD, after exclusion of heavy and binge drinkers, modest alcohol consumption (i.e., ≤20 g of alcohol per day) was associated with 44% lower risk of liver fibrosis and 34% less hepatocellular ballooning compared with nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(32) In a 2016 meta-analysis of mostly cross-sectional studies with a total of 76,608 participants, drinking alcohol up to 40 g per day was associated with a 23% reduction in prevalence of fatty liver disease. (33) In a recent prospective study of a healthy Japanese population without liver disease at baseline who were followed for up to 3 years, drinking alcohol (up to more than 40 g per day for men and 20 g per day for women) was associated with decreased incidence of fatty liver diagnosed by ultrasound imaging. (21) In a cross-sectional study of baseline data for adult patients in the Nonalcoholic Steatohepatitis Clinical Research Network with biopsy-proven NAFLD, after exclusion of heavy and binge drinkers, modest alcohol consumption (i.e., ≤20 g of alcohol per day) was associated with 44% lower risk of liver fibrosis and 34% less hepatocellular ballooning compared with nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in a healthy Japanese population using data from annual health checkups showed an inverse relationship between modest alcohol consumption (up to 40 g of alcohol per day) and risk of elevated transaminases . In a 2016 meta‐analysis of mostly cross‐sectional studies with a total of 76,608 participants, drinking alcohol up to 40 g per day was associated with a 23% reduction in prevalence of fatty liver disease . In a recent prospective study of a healthy Japanese population without liver disease at baseline who were followed for up to 3 years, drinking alcohol (up to more than 40 g per day for men and 20 g per day for women) was associated with decreased incidence of fatty liver diagnosed by ultrasound imaging .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of more than 76,000 patients demonstrated a 22% risk reduction in prevalence of nonalcoholic fatty liver disease (NAFLD) with moderate alcohol use (Fig. ) . This protection was still present when stratified by sex, geography, and presence of obesity.…”
Section: Key Pointsmentioning
confidence: 97%
“…2). 7 This protection was still present when stratified by sex, geography, and presence of obesity. In fact, the odds ratio (OR) for the presence of NAFLD in obese patients who consumed moderate amounts of alcohol was 0.687.…”
mentioning
confidence: 97%
“…FLD is caused by the excessive accumulation of fat in liver cells and can progress to cirrhosis and hepatocellular carcinoma (Reddy and Rao, 2006). The findings from a recent metaanalysis of alcohol and risk of FLD suggest that light to moderate alcohol consumption is associated with a lower risk of FLD than non-drinking whilst heavy drinking is likely to be detrimental (Cao et al, 2016). However, most previous studies included in this meta-analysis were cross-sectional (15 out of 16 studies).…”
Section: Introductionmentioning
confidence: 99%